HUBUNGAN DAUN BANGUNâ€“BANGUN TERHADAP PRODUKSI ASI PADA IBU NIFAS DI KELURAHAN SERIBU DOLOK - Husna, Nadia (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2021)
The Relationship between Daun Bangun and Wake Against Breast Milk Production in Post-partum mothers in Seribu Dolok Village in 2020â€. This type of research is descriptive analytic with a total sample of 30 postpartum mothers. Based on the results of the research above, it can be seen that the respondents who consumed the wake-wake leaves were 22 people (73%) post-partum mothers, while the respondents who did not consume the wake-wake leaves were as many as 8 people (27%) post-partum mothers. The good milk production is 25 people (83%) postpartum mothers, while the respondents whose milk production is not good are 5 people (17%) postpartum mothers using chi- square test obtained a sig value of 0.000 <Î± = 0.05, df = 2, obtained X2 count> X2 table (19.402> 5,991), this result means that there is a relationship between leaves and wake of breast milk production in postpartum mothers in the Kelurahan Thousand Dolok.